Manfaat Edukasi Pentingnya Zat Gizi Kepada Calon Ibu Hamil - Eva Fauzia; Siti Hapsah Pahira; Aisyah Nurjanah (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
Abstract – Nutrition is the main factor in determining the health value of pregnant women. Nutrition in pregnant women is influenced by knowledge, the higher the knowledge of prospective pregnant women, the lower the risk of pregnant women being affected by disorders during pregnancy. Maternal nutritional health before and during pregnancy affects the health status of herself and the developing fetus. Pregnancy is an important condition for increasing nutritional knowledge. This study aims to determine the importance of nutrition education for prospective pregnant women. The method used in this research is library research. The results obtained indicate that prospective pregnant women who receive education such as classes for pregnant women, posyandu activities, activities that contain education on nutrition and prevention of stunting mostly have good knowledge and a positive attitude. There is a significant relationship between providing nutrition education and increasing knowledge and attitudes about the importance of nutrition during pregnancy later.